Spatiotemporal auxin distribution in Arabidopsis tissues is regulated by anabolic and catabolic reactions under long-term ammonium stress - Dziewit, Kacper; Pěnčík, Aleš; Dobrzyńska, Katarzyna; Novák, Ondřej; Szal, Bożena; Podgórska, Anna (BMC plant biology, 2021)
BACKGROUND: The plant hormone auxin is a major coordinator of plant growth and development in response to diverse environmental signals, including nutritional conditions. Sole ammonium (NH4+) nutrition is one of the unique growth-suppressing conditions for plants. Therefore, the quest to understand NH4+-mediated developmental defects led us to analyze auxin metabolism. RESULTS: Indole-3-acetic acid (IAA), the most predominant natural auxin, accumulates in the leaves and roots of mature Arabidopsis thaliana plants grown on NH4+, but not in the root tips. We found changes at the expressional level in reactions leading to IAA biosynthesis and deactivation in different tissues. Finally, NH4+ nutrition would facilitate the formation of inactive oxidized IAA as the final product. CONCLUSIONS: NH4+-mediated accelerated auxin turnover rates implicate transient and local IAA peaks. A noticeable auxin pattern in tissues correlates with the developmental adaptations of the short and highly branched root system of NH4+-grown plants. Therefore, the spatiotemporal distribution of auxin might be a root-shaping signal specific to adjust to NH4+-stress conditions.
Keywords: Indoleacetic Acids; oxidace-redukce; metabolismus; Arabidopsis; Ammonium Compounds; časoprostorová analýza; amoniové sloučeniny; Auxin degradation; Auxin synthesis; Spatio-Temporal Analysis; kyseliny indoloctové; výhonky rostlin; Metabolism; Plant Shoots; Stress, Physiological; fyziologický stres; tkáňová distribuce; Oxidation-Reduction; Arabidopsis thaliana; Ammonium nutrition; Auxin conjugation; Root development; Plant Roots; kořeny rostlin; Tissue Distribution